Media Video Profile Penunjang Promosi Dan Informasi Pada SMK Harapan Jaya Kota Tangerang - Ryan Renaldi; Ani Fitriyani; Gian Rizki Illahi (UNIVERSITAS RAHARJA, 2017)
Development of science and information makes a variety of activities and life sehari–hari of the information gained from the media, both print and electronic media. The role of information technology and multimedia are also not to miss, a variety of information offered by the form of multimedia that can create interactive and informative presentation by combining text, audio, video, animation and graphics used for competitive advantage Development education grew rapidly, causing a growing number of facilities and advantages that should be promoted to compete, especially at SMK Yuppentek 4 Ciledug Tangerang. The purpose of this research is to design-based audio visual media in order to be an effective appeal, especially in the delivery of information and promotions regarding things – things that are related to the overall CMS Yuppentek 4 Ciledug Tangerang. SMK Yuppentek 4 Ciledug Tangerang is located in Tangerang. Existing problems, namely the medium used by the SMK SMK Yuppentek 4 Ciledug Tangerang was a print media, in general the community more receptive of information via media interactive and communicative, so CMS Yuppentek 4 Ciledug Tangerang requires video media profile as a media of supporting information and promotion on the show to prospective students and students of SMK Yuppentek 4 Ciledug Tangerang, or as a media information to the public , so the design of video media profile that displays the entire scope, advantages and facilities belonging to SMK Yuppentek 4 Ciledug Tangerang, can be a solution in solving problems in media promotion and information. With this author makes research with the title